Cu2ZnSnS4, a Fascinating Counter Electrode for TiO2‐Free Dye‐Sensitized Solar Cells. Issue 7 (15th February 2021) - Roy, Anurag; Sundaram, Senthilarasu; Mallick, Tapas K.
Abstract: Since innovation, different dye‐sensitized solar cells (DSSCs) have endeavored with additional components to escalate the efficiency, cost‐effectiveness and long‐term stability. Various approaches have been executed to reduce the amount of costly platinum (Pt) used in DSSCs and/or to explore cheaper alternatives to Pt. In this work, cheaper elements based quaternary chalcogenide alloy; Cu2 ZnSnS4 (CZTS) has been projected as a prominent counter electrode (CE) candidate to Pt in DSSCs. The CZTS thin film has been developed by an in‐situ synthesis employing a hydrothermal technique and further evaluating various physicochemical characterization. Our results manifest that using the CZTS CE, a power conversion efficiency (PCE) of 4.3 % was exhibited for TiO2 based photoanode. The highest PCE of 6.5 % was achieved for BaSnO3 based photoanode, a promising alternative oxide to TiO2 photoanode. This work further signifies a unique combination of newly developed BaSnO3 (BSO)‐CZTS DSSCs, could be a promising competitor to TiO2 ‐Pt DSSCs. Abstract : Investigation on the adequate performance of cheaper Cu2 ZnSnS4 (CZTS)‐based counter electrode for BaSnO3 (BSO)‐based dye‐sensitized solar cells (DSSCs), explored as an effective alternative to costly Pt and TiO2, respectively, which could elucidate more extended device performance compared to TiO2 ‐Pt‐based DSSCs. Thus, the development and evaluation of new kind of DSSC device as an alternative material to traditional Pt and TiO2 is a promising research area, which is essential to reduce the cost of commercialisation devices.